How Do We Know Teacher Professional Development Is Working? : Measuring Changes in Teaching Practices in the Classroom - Luna-Bazaldua, Diego (World Bank, Washington, DC, 2021)
The teaching that students receive in the classroom is the most important school-based determinant of student learning. The objective of this note is to provide guidance on how to: (1) establish a numerical indicator to measure changes in teaching practices through the use of classroom observation tools for use in education projects, and (2) produce a benchmark to compare changes in teaching practices through this indicator. The way that teachers interact with their students in the classroom makes all the difference in ensuring students’ academic and socioemotional learning. For this reason, education projects that seek to improve student learning frequently include components focused on improving teaching practices through interventions such as modifying the curriculum, improving pre-service or in-service teacher training, and integrating additional instructional support to the classroom through the use of structured instructional material or technology. This note provides guidance on how to establish a numerical indicator to measure teaching practices through classroom observation tools, and how to benchmark this indicator to track changes in teaching practices over time for use in educational interventions. This guidance is structured through a three-step process: step 1, selecting an appropriate classroom observation tool; step 2, selecting an indicator to track teaching practices using that tool; and step 3, establishing a reasonable benchmarking target for the chosen indicator.